2005
DOI: 10.1016/j.engstruct.2005.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical studies of external steel plate strengthened reinforced concrete coupling beams

Abstract: This paper aims to develop a new method for strengthening reinforced concrete coupling beams. Experiments were conducted to test three full-scale RC coupling beams, of which two were strengthened by bolted external steel plates on the side faces of the beams and the other one acted as a control specimen without strengthening. The improvements to strength, deformation and energy dissipation of the external plate strengthened RC coupling beams were observed from the experimental results. Nonlinear finite element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…The nonlinear finite element analysis (NLFEA), on the other hand, has become a mature and powerful tool for the comprehensive investigation of various composite structures [4][5][6]. After validated the finite element models by the well-controlled experimental results, reliable numerical results, such as full-field internal stress distributions, in far more detail than is possible in laboratory work can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear finite element analysis (NLFEA), on the other hand, has become a mature and powerful tool for the comprehensive investigation of various composite structures [4][5][6]. After validated the finite element models by the well-controlled experimental results, reliable numerical results, such as full-field internal stress distributions, in far more detail than is possible in laboratory work can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…One of the relatively new forms of composite structures is produced by anchoring steel plates on the sides of reinforced concrete beams using sets of bolt groups [1][2][3][4][5]. It is shown that, by using the steel plates, the RC beam gains additional strength and stiffness while maintaining a satisfactory level of ductility, and has been used in retrofitting reinforced concrete beams like floor beams [2] and coupling beams [5].…”
Section: Introductionmentioning
confidence: 99%
“…Testing of hybrid coupled shear wall systems at the University of McGill in Canada [7][8][9] led to recommendations for designing steel coupling beams in hybrid coupled shear wall systems. Experimental and numerical studies on concrete-steel composite coupling beams at the University of Hong Kong in China [10] were conducted to investigate the effects of encasement around shear-yielding steel coupling beams. These experimental studies were primarily concerned with the inelastic cyclic behaviour of steel coupling beams or hybrid coupled shear wall systems and did not deeply investigate connection strength.…”
Section: Introductionmentioning
confidence: 99%